If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7a + 11 = 3a + 21 Reorder the terms: 11 + 7a = 3a + 21 Reorder the terms: 11 + 7a = 21 + 3a Solving 11 + 7a = 21 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 11 + 7a + -3a = 21 + 3a + -3a Combine like terms: 7a + -3a = 4a 11 + 4a = 21 + 3a + -3a Combine like terms: 3a + -3a = 0 11 + 4a = 21 + 0 11 + 4a = 21 Add '-11' to each side of the equation. 11 + -11 + 4a = 21 + -11 Combine like terms: 11 + -11 = 0 0 + 4a = 21 + -11 4a = 21 + -11 Combine like terms: 21 + -11 = 10 4a = 10 Divide each side by '4'. a = 2.5 Simplifying a = 2.5
| 4c^3+4c^2-80c=0 | | 7x+22=9(x-4) | | 56/11 | | 2(5n+8)=-16+6n | | x+3=6(8-3x)-7 | | 7150=6.25*r*5 | | A=1/2*bh | | 5x+3y=40 | | -6a+28=-(2a-8) | | 9x^2+18x+17=0 | | 5c^3+30c-35c=0 | | 3(-8n-2)=-2n+16 | | 24x-4x^2=0 | | 3y-9=6y+3 | | 5x+5(2+6x)=10+3x | | (6+y)(3y+7)=0 | | (2x)lnx+x=0 | | -15-5r=5(1+3r) | | (5v-7)(3-v)=0 | | 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= | | x^3-10x^2+13x+74=0 | | 5b+3(3b+4)=-24+2b | | x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 | | q-1=5q+3q-8 | | 0.16=-0.4+0.7x | | 8.5+3.4= |